2018
DOI: 10.1007/s11156-018-0700-2
|View full text |Cite
|
Sign up to set email alerts
|

Executive cash compensation and tax aggressiveness of Chinese firms

Abstract: We examine the influence of corporate compensation policies on firms' tax aggressiveness in an emerging market where executive compensation is primarily in cash form. Based on a handcollected dataset of 958 firm-year observations of Chinese listed firms for the 2006-2012 period, we find that firms paying higher executive cash compensation are associated with lower tax aggressiveness. This relationship also holds for the excess cash compensation measures which control for executive shareholding, firm profitabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
38
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 91 publications
4
38
0
8
Order By: Relevance
“…This strategy can be called tax avoidance. Tax avoidance is often referred to as tax aggressiveness because companies aggressively reduce corporate taxes on income before tax (Huang, Ying, & Shen, 2018). Companies' tendency to minimize tax payments is based on the same benefits received from the government, both paying large and small amounts of tax (Huda, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…This strategy can be called tax avoidance. Tax avoidance is often referred to as tax aggressiveness because companies aggressively reduce corporate taxes on income before tax (Huang, Ying, & Shen, 2018). Companies' tendency to minimize tax payments is based on the same benefits received from the government, both paying large and small amounts of tax (Huda, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, for research related to executive compensation on corporate tax avoidance, there are differences in each study's results. The study of Huang et al (2018) revealed that if companies pay higher compensation money to executives, tax avoidance will be lower for companies registered in China. Gorry, Hassett, Hubbard, and Mathur (2015) report their empirical findings that there is a significant impact on taxes due to executive compensation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A maximização dos lucros (Mills, Erickson, & Maydew, 1998;Santana, 2014;Blaufus, Mohlmann, & Schwäbe, 2019), o aumento da remuneração dos gestores (Rego & Wilson, 2012;Wahab & Holland, 2012;Gaertner, 2014;Gul, Khedmati, & Shams, 2018;Huang, Ying, & Shen, 2018) e a busca por sistemas tributários mais simples (Elali, 2009) são apontados na literatura como fatores motivacionais para realização da prática.…”
Section: Introductionunclassified